2019
DOI: 10.1186/s13287-019-1368-9
|View full text |Cite
|
Sign up to set email alerts
|

Human amniotic epithelial cells improve fertility in an intrauterine adhesion mouse model

Abstract: Background Intrauterine adhesion (IUA) is an adhesion of the uterine cavity or cervical canal resulting from damage to the basal layer of the endometrium; this condition is usually accompanied by fibrosis of the endometrium. Previous studies have demonstrated that human amniotic epithelial cells (hAECs) have stem cell characteristics; however, it is unclear whether hAECs have the therapeutic potential to restore fertility after IUA. Methods A murine IUA model was establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 40 publications
3
85
0
2
Order By: Relevance
“…The injury of normal endometrium in IUAs makes the epithelial cells and interstitial glandular cells rich in ERα disappear; however, the expression of ERα in the basal layer and even SM layer is relatively less, resulting in the trauma site that is not sensitive to estrogen stimulation. Some recent studies have confirmed that the expression of ER in the endometrial tissue of IUAs is significantly decreased [18,29].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The injury of normal endometrium in IUAs makes the epithelial cells and interstitial glandular cells rich in ERα disappear; however, the expression of ERα in the basal layer and even SM layer is relatively less, resulting in the trauma site that is not sensitive to estrogen stimulation. Some recent studies have confirmed that the expression of ER in the endometrial tissue of IUAs is significantly decreased [18,29].…”
Section: Discussionmentioning
confidence: 97%
“…Among these MSCs, hUC-MSCs are preferred in that they can be collected easily, non-invasive, and no ethical constraints; they can secrete various cytokines and trophic factors; and they are immunoprivileged [ 9 , 10 ]. About IUAs, the current studies tend to focus on the efficacy of MSCs [ 17 , 18 ]. However, studies on the distribution of hUC-MSCs in the uterus of IUAs after cell transplantation are far from well elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their plasticity and immunomodulatory properties, hAESCs have been considered for treatment of a broad variety of conditions, including lung fibrosis [ 40 , 115 , 131 , 149 , 151 , 152 , 153 , 154 ], spinal cord injuries [ 60 ], Parkinson’s disease [ 64 ], Alzheimer’s disease [ 155 ], diabetes [ 69 ], wound healing [ 147 , 148 , 156 ], liver fibrosis [ 75 , 157 , 158 , 159 ], autoimmune uveitis [ 135 ], Hashimoto’s thyroiditis and systemic lupus erythematosus [ 134 ], and intrauterine adhesions [ 160 , 161 , 162 ]. Among these preclinical trials involving hAESCs, autoimmune diseases make up a large proportion, presumably because of the tremendous effect of immunomodulation.…”
Section: The Therapeutic Potential and Clinical Advances Of Human mentioning
confidence: 99%
“…As promising seed stem cell, hAECs have been widely used to treat various diseases through transplantation therapy. Evidence supported by animal studies has revealed that hAECs show therapeutic potential for treatment of many diseases, including neurological disorders [ 1 4 ], lung injury [ 5 , 6 ], liver injury [ 7 ], diabetes [ 8 ], acute kidney failure [ 9 ], cardiovascular diseases [ 10 ], wound healing [ 11 ], healing of stage III pressure ulcers [ 12 ], intrauterine adhesion [ 13 ], and premature ovarian failure (POF) [ 14 ]. Although hAECs have exhibited good therapeutic efficacy, they possess differences in differentiation potential, secretory function, and immunomodulatory activity under different conditions, producing specific effects depending on their application.…”
Section: Introductionmentioning
confidence: 99%